Knowledge and application of cardiovascular disease prevention guidelines among family physicians: a cross-sectional study - Korzh, Oleksii; Nikolenko, Yevgenii; Titkova, Anna; Lavrova, Yelizaveta; Vovk, Kira (Skopje-Warsaw : Scientific Foundation SPIROSKI, Sciendo, 2021)
Family physicians (FPs) play an important role in the prevention of cardiovascular disease (CVD). A self-administrated questionnaire was administered, exploring demographic, job characteristics, knowledge of CVD prevention guidelines, and application of CVD guidelines’ questions about the essential items related to diagnosis and management of CVD according to the international/local guidelines. RESULTS: The results show a very low level of knowledge of guidelines among FPs with 85.8% scoring below the acceptable knowledge level. The guidelines were applied below the acceptable level with 51.3% scoring below the cutoff point. The results indicate that both average scores were below the minimum acceptable level. Lack of knowledge of the CVD preventive care was considered the biggest barrier (62.8%). Lack of counseling skills was the second major barrier (37.9%). Subjectivity of the questions was considered to be the third barrier (32.6%). Lack of counseling skills was the second major barrier (37.9%). Subjectivity of the questions was considered to be the third barrier (32.6%). Low levels of knowledge and implementation of guidelines among primary care providers can be recognized and addressed through education, training, and monitoring of their implementation.
Keywords: MEDICINE; cardiovascular disease; prevention; guidelines; primary care; knowledge